2004
DOI: 10.1901/jaba.2004.37-481
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Response Allocation in Individuals With Multiple Forms of Stereotyped Behavior

Abstract: Three experiments were conducted to evaluate response allocation of stereotypy during free-operant and restricted-operant conditions. Five children with autism or related developmental disabilities participated in at least one and up to three of the experiments. In Experiment 1, the stereotypic response that emerged as most probable during a free-operant phase was restricted, and response allocation was again evaluated. The results for 3 participants showed that restricting the high-probability response was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 28 publications
8
73
1
1
Order By: Relevance
“…In addition, functional play skills and social engagement simultaneously increased during the restricted interest play activity. This finding is consistent with research suggesting that it may be possible to produce an increase in functional play skills by implementing play activities that utilize aspects similar to the stereotyped behavior Lang et al 2010a, b;Rapp et al 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, functional play skills and social engagement simultaneously increased during the restricted interest play activity. This finding is consistent with research suggesting that it may be possible to produce an increase in functional play skills by implementing play activities that utilize aspects similar to the stereotyped behavior Lang et al 2010a, b;Rapp et al 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Austin exhibited repetitive behaviors that involved organizing, sorting, and lining up items by shape, size, or color. Based on the topography of his repetitive behaviors, we chose socially appropriate play activities that matched aspects of his stereotypy Rapp et al 2004). These play activities included games such as Connect Four®, Kerplunk® (which involve lining up game pieces as part of the game play), and stacking wooden beads of different shapes and colors on a pole to create a variety of patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, it is possible that the high levels of in vocal stereotypy that were observed during the last two sessions of the GC condition may be a result of deprivation (for the product of vocal stereotypy) that was imposed when reprimands were delivered for vocal stereotypy in the RC condition (see Rapp, 2007). A handful of studies, which did not employ specific antecedent stimuli, have found that automatically reinforced behavior often increases following periods of response restriction or reduction (e.g., Himle, Woods, Concelea, Bauer, & Rice, 2007;Rapp, Vollmer, Dozier, St. Peter, & Cotnoir, 2004;Rapp, 2006Rapp, , 2007. Therefore, it is not clear whether the GC developed evocative properties for Al's vocal stereotypy as a result of the consequences that were delivered in the presence of the RC.…”
Section: Resultsmentioning
confidence: 99%
“…For the other participant, the results indicated that hand flapping occurred only when social interaction was provided noncontingently. Although these studies showed that antecedent stimulation of various modalities (e.g., audio, vibratory) may function as establishing conditions for engagement in automatically reinforced behavior, the results are somewhat limited in that each study evaluated individuals with only one or two forms of problem behavior and only the Van Camp et al (2000) study evaluated multiple forms of stimulation.In a recent study of individuals who displayed multiple forms of automatically reinforced behavior, Rapp, Vollmer, St. Peter, Dozier, and Cotnoir (2004) found that blocking or limiting access to the most probable behavior (the one that occurred for the highest percentage of time) produced orderly and dynamic changes in subsequent time allocation to other behavior. For two participants, one untargeted behavior decreased and another untargeted behavior increased when the most probable behavior was blocked.…”
mentioning
confidence: 99%
“…If Andy's body rocking was elicited then punishment in the form of brief TV loss would not be expected to decrease this behavior. Conversely, if Andy's behavior was operant, and access to the TV was a potent reinforcer, then contingent TV loss should decrease body rocking, increase other (possibly stereotypic) behavior, or both (see Rapp et al, 2004). Subsequently, time-out was implemented contingent on hand flapping to determine whether Andy would reallocate time to body rocking when hand flapping was punished.…”
mentioning
confidence: 99%